The Effect of Apparatus Empowerment on Employee Performance in the Government Sector - Nusi, Marten; Razak, Darmawaty Abd; Prahara, Sandi (IJESS International Journal of Education and Social Science, 2024)
This study aims to determine the Impact of Apparatus Empowerment on Employee Performance in the Government Sector. This study used a sample of 27 people. The data analysis used is Simple Linear Regression. The results of the hypothesis test between Apparatus Empowerment (X) on Employee Performance (Y) at the Ponelo Islands Sub-district Office, North Gorontalo Regency, obtained a sig value for the influence of the Apparatus Empowerment variable on Employee Performance obtained at 0.000 while the value was 0.05. If the two values are compared, the sig value (0.000) is still smaller than the value (0.05). Therefore, it was concluded that Apparatus Empowerment was positive and significant for Employee Performance at the Ponelo Islands Sub-district Office, North Gorontalo Regency. The amount of influence of Apparatus Empowerment on Employee Performance at the Ponelo Islands Sub-district Office, North Gorontalo Regency is 59.3%. While the remaining 40.7% was influenced by other factors or variables that were not studied in this study.